Analysis of the representation of female athletes in sports media: a systematic literature review - AREF VAI; Caly Setiawan; Ngatman; ROLA ANGGA LARDIKA; Eddy Noviana; Jamaludin Yusuf; Sofyan Ardyanto; Mega Widya Putri; Wahyu Eko Widiyanto; Elsya Desviyanti (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The focus of coverage on female athletes is starting to shift, with more recognition of the achievements and dedication to Sports. Despite improvements in representation, there is still a gap in public recognition of female athletes compared to males, specifically in sports awards or promotional platforms.